2014
DOI: 10.1177/0960327114532384
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxicity in rabbits after a low-level exposure to diazinon, propoxur, and chlorpyrifos

Abstract: Lethal cardiac complications leading to death and various arrhythmias have been reported after organophosphate and/or carbamate poisonings. The present study focuses on the long-term effects of repeated low-level exposure to diazinon, propoxur, and chlorpyrifos (CPF) on cardiac function in rabbits. The yearly based experimental scheme of exposure consisted of two oral administration periods, lasting 3 months and 1 month each, interrupted by an 8-month washout period (total duration 12 months). At the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 59 publications
0
37
0
1
Order By: Relevance
“…Contrary to earlier AHS evaluations, we also saw no evidence of an association between lung cancer and chlorpyrifos (Alavanja et al 2004; Lee et al 2004) or carbofuran (Alavanja et al 2004; Bonner et al 2005) use. There is experimental mechanistic evidence that chlorpyrifos can induce oxidative stress and oxidative DNA damage (Ojha and Srivastava 2014; Zafiropoulos et al 2014) and that carbofuran may be genotoxic (Mladinic et al 2012). The proportion of AHS cohort members using either chlorpyrifos or carbofuran has declined since enrollment (Hoppin et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to earlier AHS evaluations, we also saw no evidence of an association between lung cancer and chlorpyrifos (Alavanja et al 2004; Lee et al 2004) or carbofuran (Alavanja et al 2004; Bonner et al 2005) use. There is experimental mechanistic evidence that chlorpyrifos can induce oxidative stress and oxidative DNA damage (Ojha and Srivastava 2014; Zafiropoulos et al 2014) and that carbofuran may be genotoxic (Mladinic et al 2012). The proportion of AHS cohort members using either chlorpyrifos or carbofuran has declined since enrollment (Hoppin et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…They reported higher levels of cholesterol, IL-1β, IL-2, IL-10, IFN-γ and Rantes in plasma, supporting the evidence that the modifications detected in adult rats may be the result of epigenetic alterations occurring during the neonatal age, leading to alterations in chemokines related to cardiac function. Zafiropoulos et al evaluated the effect of repeated low-level exposure to diazinon, propoxur and chlorpyrifos on the cardiac function of rabits and showed that these produce modifications in genomic DNA from cardiac tissues and increase the oxidative stress ( 95 ). In another study, following the administration of omethoate to rats, it was shown that the TNF-α level in cerebral tissue was significantly higher than that observed in the control group ( 96 ).…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…Hematoxylin stains the nuclei within cells blue and eosin stains the cytoplasm of cells pink. Results from histopathology tests help to clarify in combination with genotoxicity tests, the adverse effects from the exposure of chemical substances, such as pesticides, and their potential impact as shown in various studies (Abdel-Tawab et al, 2015, Marx-Stoelting et al, 2015, Tsitsimpikou et al, 2013, Zafiropoulos et al, 2014. The possible toxic outcome when one or more chemical substances are applied together is the result of agent-to-agent interactions, toxicodynamic and toxicokinetic interactions.…”
Section: Introductionmentioning
confidence: 99%